Overview of Contamination STH (Soil Transmitted Helminths) Eggs on Cabbage (Brassica oleracea (L.) in Sentra Antasari Market at Banjarmasin - Mahda Wasila; Rahmat Wirayudha; Jhudi Bonosari Soediono (Health Media, 2020)
Helminths infection is the most common infection happens in Indonesia. It is caused by intestinal netamodes which is transmitted through soil (Soil Transmitted Helminths). These nematodes need soil to reach its infective stage. Helminths group that often contaminate vegetables are Ascaris lumbricoides, Trichuris trichiura, and Hookworm. Most of popular vegetable is easily contaminated by STH eggs is cabbage. Cabbage is usually being eaten in raw, in this case it can cause helminths infection. This research is conducted to overview the contamination of STH eggs on cabbage that sells in Pasar Sentra Antasari Banjarmasin. This study was descriptive survey and sampling technique is used in this study was purposive sampling. The microscopic examination of STH eggs was done by sedimentation method. The result showed that 2 (11,8%) of 17 samples from market were found positive contaminated by STH eggs. The contaminants were the eggs of Ascaris lumbricoides (5,9%) and Trichuris trichiura (5,9%). Wash and cook the vegetables before consumption as prevention efforts to avoid helminths infection